Analysis of the growth of seaweed (Eucheuma cottonii) on the initial weight and different plant distance cultured off the base of waters of lingayan island - Rukka, Andi Heryanti; Masyahoro, Abdul; Samsul, Yusri (Jurnal Ilmiah Samudra Akuatika, 2022)
The aim of this study was to determine the growth of E. cottonii seaweed at different initial weights and spacings that were cultivated off the bottom of the waters. Seaweed seedlings of E. cottonii were reared for 42 days. This study used a RAL with a factorial pattern which consisted of 2 factors, namely factor J (planting distance) and factor B (seed weight). Factor J consisted of 3 levels (20 cm, 30 cm and 40 cm) and factor B consisted of 3 levels (50 g, 75 g and 100 g), so that 27 experimental units were obtained. The data were analyzed for variance before being tested for the fulfillment of the basic assumptions of analysis of variance, namely the Kolmogorov-Smirnov data distribution test, the Bartlett treatment similarity test and the Tukey Method model additiveness test using excel and Minitab 16 application programs. The results showed that the difference in plant spacing had no effect (P>0.05) on the absolute perturbation weight. The highest treatment combination was found in the combination of 30 cm spacing with an initial weight of 50 g (J2B3) and the lowest was in the combination of 30 cm spacing with an initial weight of 100 g (J2B1). Differences in initial weight (50, 75 and 100 g) had a very significant effect (P<0.01) on absolute weight growth. The higher the initial weight used, the absolute weight growth of E. cottonii increased with an increase in average weight ranging from 260.34 to 435.92 grams.